Germacrone protects against oxygen-glucose deprivation/reperfusion injury by inhibiting autophagy processes in PC12 cells - Jianxing Zhang; Li Yuan; Sujie Wang; Jiang Liu; Huiqin Bi; Guojuan Chen; Jingjing Li; Lili Chen (BMC, 2020)
Abstract Background Germacrone is an anti-inflammatory ingredient in the Chinese medicine zedoary turmeric. The purpose of this study was to explore the protective mechanism of germacrone against PC12 cells injury caused by oxygen-glucose deprivation/reperfusion (OGD/R). Methods OGD/R injury model of PC12 cells was established by using OGD/R (2 h/24 h). The cell viability was assessed by MTT assay and LDH release. The ultrastructure of cells was observed by transmission electron microscopy (TEM). The expression of autophagy related proteins in cells was determined by Western Blot. Results The results of ultrastructural observation showed that PC12 cells damaged by OGD/R showed typical autophagy characteristics. In addition, OGD/R observably up-regulated the expression of autophagy related proteins: the class III type phosphoinositide 3-kinase (PI3K III), light chain 3(LC3), and Beclin-1 in PC12 cells, and inhibited the expression of the class I type phosphoinositide 3-kinase (PI3K I), Protein kinase B (Akt), the mammalian target of rapamycin (mTOR), and B-cell lymphoma 2(Bcl-2) proteins. Furthermore, germacrone increased the cell viability of OGD/R-damaged PC12 cells by down-regulating the expression of LC3 protein in cells in a concentration-dependent manner. More importantly, germacrone significantly inhibited the expression of PI3K III, LC3, and Beclin-1 in OGD/R-injured PC12 cells, and up-regulated the expressionof PI3K I, Akt, mTOR, and Bcl-2 proteins in cells, and this inhibited or up-regulated effect was reversed by PI3K I inhibitor (ZSTK474). Conclusion The above results indicated that germacrone could inhibit the autophagy effect in OGD/R injury model of PC12 cells, the mechanism of inhibition was regulated by PI3K III/Beclin-1/Bcl-2 and PI3K I/Akt/mTOR pathways, thereby improving the cell viability of PC12 cells and playing a neuroprotective role, which provided a new drug for the treatment of OGD/R.